Initial results of a new generation dual source CT system using only an in-plane comb filter for ultra-high resolution temporal bone imaging - Meyer, Mathias; Haubenreisser, Holger; Schad, Lothar R.; Schönberg, Stefan; Henzler, Thomas (European radiology, 2014)
Objectives: To prospectively evaluate radiation dose and image quality of a third generation dual-source CT (DSCT) without z-axis filter behind the patient for temporal bone CT. Methods: Forty-five patients were either examined on a first, second, or third generation DSCT in an ultra-high-resolution (UHR) temporal bone-imaging mode. On the third generation DSCT system, the tighter focal spot of 0.2 mm2 removesthe necessity for an additional z-axis-filter, leading to an improved z-axis radiation dose efficiency. Images of 0.4 mm were reconstructed using standard filtered-back-projection or iterative reconstruction (IR) technique for previous generations of DSCT and a novel IR algorithm for the third generation DSCT. Radiation dose and image quality were compared between the three DSCT systems. Results: The statistically significantly highest subjective and objective image quality was evaluated for the third generation DSCT when compared to the first or second generation DSCT systems (all p < 0.05). Total effective dose was 63 %/39 % lower for the third generation examination as compared to the first and second generation DSCT. Conclusions: Temporal bone imaging without z-axis-UHR-filter and a novel third generation IR algorithm allows for significantly higher image quality while lowering effective dose when compared to the first two generations of DSCTs.